Progress in Radiotherapy for Cholangiocarcinoma - Wang, Ningyu; Huang, Ai; Kuang, Bohua; Xiao, Yu; Xiao, Yong; Ma, Hong (Frontiers in Oncology, 2022)
Cholangiocarcinoma (CCA) originates from the epithelium of the bile duct and is highly malignant with a poor prognosis. Radical resection is the only treatment option to completely cure primary CCA. Due to the insidious onset of CCA, most patients are already in an advanced stage at the time of the initial diagnosis and may lose the chance of radical surgery. Radiotherapy is an important method of local treatment, which plays a crucial role in preoperative neoadjuvant therapy, postoperative adjuvant therapy, and palliative treatment of locally advanced lesions. However, there is still no unified and clear recommendation on the timing, delineating the range of target area, and the radiotherapy dose for CCA. This article reviews recent clinical studies on CCA, including the timing of radiotherapy, delineation of the target area, and dose of radiotherapy. Further, we summarize large fraction radiotherapy (stereotactic body radiotherapy [SBRT]; proton therapy) in CCA and the development of immunotherapy and the use of targeted drugs combined with radiotherapy.